Korelasi Faktor Pemicu Kebiasaan Jajan Anak SD Al Khairiyah di Kecamatan Sunggal Kabupaten Deli Serdang - Nur Asni Arti; Suprianto Suprianto (Journal of Indah Science and Clinic, 2020)
Behavior originates from the impulse in humans which is an effort to meet human needs. Eating behavior that is often a problem is eating habits in canteens or stalls around school and eating fast food habits. The role of snacks in contributing energy or energy and protein substances is very significant, considering that school children get less protein intake and often snack, it is better if the snacks sold in the school canteen are high protein foods.This study aims to determine the factors associated with habitual snacking behavior. This was a non-experimental study through survey and observational approaches with a cross sectional sample of 96 students. Data collection includes eating habits, nutritional knowledge, breakfast habits, breakfast frequency, food carrying habits, pocket money, and types of food obtained through questionnaires. The data analyzed using Chi Square test. There are a relationship between nutritional knowledge, breakfast habits, carrying food, pocket money, and types of snacks with the snack habits of Al-Khairiyah Elementary School children, Sunggal District, Deli Serdang Regency. All factors are related to eating habits.